Mitigating confined blast response of buried steel box structure with foam concrete. (December 2021) - Wang, Xiaojuan; Zhang, Xuejian; Song, Luyao; Zhou, Hongyuan; Wang, Yonghui; Zhang, Hong; Cong, Pengli
Abstract: The demand and application of buried structures have greatly increased recently. With space partially or fully confined, the safety of buried structures subjected to internal hazards such as explosions is a major concern. In the present study, confined blast mitigation effectiveness of buried steel boxes with foam concrete is experimentally and numerically investigated. Tests with and without foam concrete layer applied to buried steel boxes were conducted, with which numerical models were established and validated. Factors influencing the mitigation effectiveness, such as the crushing strength and thickness of foam concrete, loading density, are examined and discussed in detail. It is found that for typical loading density, applying foam concrete layer effectively mitigates confined blast. The protection effectiveness in terms of steel box deformation improves with increasing foam concrete crushing strength and thickness. Ineffective or even negative mitigation may occur if the foam concrete layer is insufficient, which should be identified and avoided. Highlights: The effectiveness of confined blast mitigation with foam concrete is investigated. Foam concrete of proper crushing strength and thickness effectively mitigates blast. Insufficient foam concrete layer may cause greater response of protected box.